“There is No Such Finis Ultimus”: Liberal Anthropology and Church-State Relations Considered - Ellison, Michael (Dianoia: The Undergraduate Philosophy Journal of Boston College, 2025)
This paper explores the relationship between the Church and the state in the tradition of political liberalism. I analyze how that relationship is grounded in a philosophical anthropology common to liberal thinkers such as Thomas Hobbes, John Locke, and John Rawls. It then critiques the liberal view from a Thomistic perspective in two parts. First, it presents an alternative anthropology taken from the work of Aquinas himself. Secondly, it gives one possible alternative conception of the relationship between the Church and the state, namely Pope Leo XIII's confessional state. The paper concludes with a brief consideration of the obstacles facing a wider acceptance of Thomistic anthropology within the pluralism and political liberalism of modern society.